Water dispersion materials on epoxy resin basis - Домніченко, Раїса Григорівна; Мережко, Ніна Василівна; Свідерський, Валентин Анатолійович; Миронюк, Олексій Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
At present the most widely used and accessible filming agents for the water dispersion systems are the emulsions of acrylic polymers. The high atmosphere resistance and adhesion to the various substrates characterize their coating. However, they have small fade index, furrow and rigidity resistance. The aim of the work was the emulsions obtaining on the basis of epoxy resin in the water by disperse method; stabilization of dispersions obtained; and material optimization according to the sediment and coagulating stability. As a result the disperse technology of obtaining of epoxy resin emulsions was improved. In particular, the stabilizer with the optimal meaning of hydrophilic-lipophilic balance was chosen; the modes of dispersion were optimized using the method of the full factorial experiment. The rheological compatibility was analyzed. On the basis of stabilized emulsion the composition coating was made. It is characterized by the high adhesion to mineral, metal and plastic substrates. Thus, the method of stable emulsions obtaining of epoxy resin of disperse type was created. The materials may be used as filming agents to create rigid and wear-resistant coatings. In case of combination with acrylic elements one may use them for the high atmospheric resistance coating.